Loud Silence: Older adults in Canadian policy discourse - Veselka, Mercedes; Balyasnikova, Natalia (Language and Literacy / Langue et littératie, 2026)
Older adults’ literacy is of increasing concern based on the most recent International Adult Literacy Survey (OECD, 2024). In this paper, the authors apply critical policy analysis (Ball, 1993) and critical gerontology (Schmidt-Hertha et al., 2022) frameworks to examine two national Canadian policy texts, Skills for Success and ABC Life Literacy. The analysis suggests there is a glaring lack of recognition of older adults as literacy learners in these documents. There was evidence of narrowed definitions of literacy alongside stereotypical understandings of aging. The paper will be particularly relevant to policy makers and professionals that support older adults’ literacy development.